A colony count model for the control of drinking water distribution systems - Kerneis, A.; Déguin, A.; Feinberg, M. (Revue des sciences de l'eau / Journal of Water Science, 1996)
The purpose of this study is to select a process control parameter for monitoring microbial regrowth in a network and to develop a more accurate and relevant quality control of supply water. Two parameters were examined as potential process control parameters: the water residence time in the network and the concentration of biodegradable organic matter. Residence time calculations were carried out and validated by tracer studies in a branched network and then in a simply looped network. The measurement of the natural dissolved organic carbon (DOC) consumption in the network was preferred to the determination of any in vitro biodegradation. The measurement of consumption requires the determination of DOC in treated water and in supply water. It is simpler and less expensive than other biodegradable organic matter determinations. A model for colony counts as a function of the residence time was developed in order to demonstrate that this parameter can be used for process controlling. This model was very well adjusted to data collected in a network in winter, spring and summer. This process control parameter was then used in order to locate and estimate the quantity of water whose colony counts exceed the European directive guide level.Accurate correlation measurements between colony counts and DOC consumed in the network were carried out in three distinct systems. No significant correlations were measured. For these three networks, biodegradable organic matter measurements based on DOC determinations were demonstrated to be unreliable process control parameters for monitoring bacterial regrowth.